Ending the Accounting-for-Intangibles Status Quo. Issue 4 (8th August 2019) - Lev, Baruch
Abstract: The surge of corporate intangible investments is the hallmark of developed economies, radically transforming the business models, strategies, and performance of business enterprises. Accounting standard-setters, however, by and large, are oblivious to this world-wide development. I establish in this study that this accounting resistance to change seriously harms investors and the economy-at-large, and accordingly I propose feasible remedial changes to the accounting system to adapt it to economic reality. I discuss implementation issues of the proposed change, and the reasons for the three-decade resistance of accounting standard-setters to change the accounting of intangibles. Finally, in order to facilitate the accounting change, I outline a wide-ranging, policy-oriented research agenda on intangibles and related issues.